Antibiotic Susceptibility Pattern of Extended-Spectrum Beta-Lactamase-Producing Klebsiella Pneumoniae and Escherichia Coli - Erlina Wahyu Elmawati; Dewi Indah Noviana Pratiwi; Noor Muthmainah; Agung Biworo (Indonesian Association of Clinical Pathologist and Medical laboratory, 2021)
Extended-Spectrum Beta-Lactamase (ESBL) producing bacteria is a type of resistance that leads to complex management of patients in intensive care due to their resistance to first, second, and third-generation Cephalosporin and monobactam antibiotics. The most ESBL-producing bacteria are found in the family Enterobacteriaceae, especially Klebsiella pneumoniae and Escherichia coli. The purpose of this research was to determine the sensitivity pattern of ESBLproducing bacteria in Intensive Care Units (ICUs) of Ulin Hospital, Banjarmasin, in the period of 2016-2018. This research was a descriptive study with a cross-sectional approach using data from the laboratory medical records of patients with positive ESBL in the ICUs of Ulin Hospital, Banjarmasin, between 2016 and 2018. The research sample was taken by the total sampling method. This research obtained 216 isolates of ESBL-producing bacteria consisting of 155 (71.8%) isolates of Klebsiella pneumoniae and 61 (28.2%) Escherichia coli. It was found that the Cephalosporin antibiotics (Cefazolin, Ceftazidime, Ceftriaxone, and Cefepime) and monobactam antibiotic (Aztreonam) had the lowest sensitivity. Aminoglycoside antibiotics (Amikacin), Carbapenem (Ertapenem and Meropenem), and Tetracycline (Tigesycline) were the most sensitive antibiotics. It was concluded that both Klebsiella pneumoniae and Escherichia coli were the most dominant ESBL-producing bacteria and showed good sensitivity to the Amikacin, Ertapenem, Meropenem, and Tigecycline.